2021
DOI: 10.22141/2224-0713.4.98.2018.139427
|View full text |Cite
|
Sign up to set email alerts
|

Місце Центральних Міорелаксантів У Лікуванні Неспецифічного Болю В Спині

Abstract: Місце центральних міорелаксантів у лікуванні неспецифічного болю в спині Резюме. У роботі розглянуто сучасні стратегії фармакологічного лікування неспецифічного болю в спині. Показано, що, незважаючи на деякі контраверсійні підходи до лікування згідно з останніми клінічними рекомендаціями, центральні міорелаксанти продовжують займати значне місце у лікуванні болю в спині. У той же самий час ненаркотичні анальгетики (парацетамол) вже не вважаються препаратами першої лінії терапії гострого болю в спині, як це бу… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Similar LC-ESI-MS method was reported by Jeoung et al for determination of Eperisone in human plasma using a solvent extraction technique and Tolperisone as internal standard. The limit of detection for analyte was found to be 0.1 pg/ml for Eperisone with a linear range from 0.01 to 10.0 ng/ml [9]. Ding et al also utilized the liquid extraction technique and similar The LOD was found to be 0.5 ng/ml with a linearity in the range of 1-500.0 ng/ml (r 2 = 0.999), for Eperisone, Tolperisone and Tizanidine.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similar LC-ESI-MS method was reported by Jeoung et al for determination of Eperisone in human plasma using a solvent extraction technique and Tolperisone as internal standard. The limit of detection for analyte was found to be 0.1 pg/ml for Eperisone with a linear range from 0.01 to 10.0 ng/ml [9]. Ding et al also utilized the liquid extraction technique and similar The LOD was found to be 0.5 ng/ml with a linearity in the range of 1-500.0 ng/ml (r 2 = 0.999), for Eperisone, Tolperisone and Tizanidine.…”
Section: Discussionmentioning
confidence: 98%
“…Eperisone also possess some vasodilator activity and antinociceptive effects [5][6][7][8] . Although the use of centrally acting muscle relaxants is associated with undesirable side effects like drowsiness, dizziness and ataxia, but still they are widely prescribed alone or in combination with analgesics for the management of muscle spasms and myalgias, more commonly lower back pain [9][10][11][12] . Eperisone because of its mechanism of action, is comparatively devoid of the undesirable side which are usually associated with intake of centrally acting muscle relaxants 7,8,[13][14][15] .…”
mentioning
confidence: 99%